THE USE OF AUDIOVISUAL METHODS TO IMPROVE SPEAKING SKILLS AT THE CENTER FOR PROMOTION OF FOREIGN LANGUAGES, PAITON PROBOLINGGO - Rahman, Ahmad Fauzi; Wijaya, Muallim (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to describe the speaking skills of students who are taught using film media in learning Arabic, as well as to determine the development of speaking skills in students of the Center for Foreign Language Promotion. , reading skills, and writing skills are the four skills in Arabic. . Speaking skills are one of the basic skills that students must master when learning Arabic. Film media is a form of entertainment that not only provides entertainment to the audience but also helps facilitate social and class communication, and determines the level of fluency of a person in communicating in Arabic.